Evaluation on Massive Open Online Courses (MOOC) awareness and readiness among radiographers in Malaysia /Muhammad Mukhriz Roslan, Shahrani Janudin and Lyana Shahirah Mohd Yamin - Roslan, Muhammad Mukhriz; Janudin, Shahrani; Mohd Yamin, Lyana Shahirah (UiTM Press, 2018)
This study focuses on the use of online quizzes and gamification in enhancing students' motivation at the AkademiLaut Malaysia (ALAM), particularly for Diploma in Nautical Studies programme. This exploratory study aims to reap the benefits of using learning technologies such as the online quizzes and gamification in maritime education and training. As the International Maritime Organisation(IMO) Standards of Training and Certification for Watchkeeping(STCW) syllabus covers vast areas of sea navigation, seamanship, safety and shipping (maritime knowledge and competencies), it is timely to promote digital learning methods in classroom especially those that could increase students' motivation in learning. The results of quantitative study on 152 respondents of first year nautical cadet officers showed that online quizzes and gamification were the preferred delivery . methods in classroom compared to other methods used. Finally, the results of study also proved that online quizzes and gamification were significant in enhancing students' motivation. This has a significant impact on current policy and teaching and learning strategies for Maritime Education and Training (MET).